CONSTRUCTING FLASH FLOOD DISASTERS IN GREENPEACE INDONESIA’S INSTAGRAM POSTS: A MULTIMODAL APPRAISAL DISCOURSE ANALYSIS - Astri Dwi Floranti (Universitas Muhammadiyah Tapanuli Selatan, 2026)
This research explores the portrayal of flash flood disasters in Sumatra and Aceh through Greenpeace Indonesia’s Instagram posts by employing a multimodal appraisal discourse analysis. The research incorporates the Attitude system from Appraisal theory to assess verbal evaluations and visual grammar to investigate ideational visual representation. By utilizing a qualitative multimodal discourse analytical framework, the data consist of selected Instagram posts related to flash flood disasters. The results indicate that captions predominantly express negative Judgment and Appreciation, depicting political, corporate, and institutional figure as irresponsible and ineffective, while Affect is used selectively to emphasize the suffering of disaster victims. Visually, the posts dominantly use conceptual and symbolic representations that frames environmental destruction as a more extensive and systemic issue. The interplay between the verbal and visual elements portrays floods as crises that are socially created and morally accountable rather than as natural disasters that are unavoidable. Through this narrative, Greenpeace advocates for environmental justice, political accountability, and ethical responsibility. This research verifies that multimodal appraisal discourse analysis serves as a valuable approach for investigating environmental activism in digital platforms.